The use of mobile text messaging as a behavioural intervention to increase physical activity in adults with T2DM in Saudi Arabia - Alsahli, Mohammed (2022)
This feasibility study has informed the suitability of the protocol design for a future full-size RCT. Our findings have demonstrated that the research processes for our feasibility design have been feasible and acceptable. Our collected data demonstrated a small but statistically significant increase in exercise self-efficacy, physical activity levels and barriers to physical activity, although these findings need to be confirmed by randomised experimental trials in the future.